Sala de Aula Invertida no ensino de Cálculo Diferencial e Integral I em cursos de Engenharia: Uma proposta experienciada - Pinheiro, Geovane Duarte (2022)
The teaching of Calculus has been the subject of scientific work overtime. The approach of this research was to investigate the practice itself by applying the flipped classroom method in Calculus for Civil Engineering, Electrical Engineering, and Mechanical Engineering courses in a private teaching institution to understand the possible contributions of this methodology and considerations to the teaching and learning processes. Based on the contextualization of calculus instruction in Mathematics Education research and the history of the discipline in engineering courses, it was possible to find the active methodologies and digital technologies that have been used in engineering courses in the last decade through a systematic review of the literature. Based on the Flipped Classroom, the study of the practice itself was conducted with two groups of the engineering course in the Calculus discipline. Digital technologies such as videos, slides, and a virtual learning environment were used to conduct the pre-class moments and provide the students with the pre-study material. A diary was used to record perceptions throughout the process. The main findings showed that the flipped classroom method provides a collaborative and interactive classroom environment that can potentially be combined with other teaching methods. The material previously provided to the students was also helpful to them as they could access it at any time for their studies. Although student engagement and participation improved during class, the average agreement rate was 59%, indicating that there is still a need to explore different methods in combination with the use of digital technologies to support both the planning and execution of classes and to help students in their studies.